An Analysis of Code Switching on English Language Learning - Ni Kadek Dewi Puspita Yanti (Jurnal Penelitian Mahasiswa Indonesia, 2022)
Language is an important communication tool in the learning process that occurs in the classroom. One of the languages ​​taught in schools is English, but English is a foreign language for students. As a result, some teachers utilize code switching in the classroom to assist students learn English. With respect to this occurrence, the purpose of this research is to describe 1) the sorts of code-switching that occur in class activities; (2) code switching function that happen in class activities; (3) ) the factors that contribute to the increased usage of code-switching in English learning; and (4) the impact of code-switching on English language learning. This research uses library research method. Literature study could be an information collection strategy by conducting a review study consider of books, literatures, notes, and reports that have to be do with the issue being solved. In this paper, literature study technique is used to collect theoretical data. Code switching gives a positive impact on English language learning. It makes a difference learner to get it the difficult aspects of the lessons being instructed and thus able to take after the enlightening given. When the teacher clarifies what is stated in the native language or first language, it encourages students to pay attention, especially those who struggle with English. Moreover, code switching aids students in expressing their ideas when they are unable to do it in English. Furthermore, code switching aids not only students but also teachers in managing the classroom.